Acute food insecurity and short-term coping strategies of urban and rural households of Bangladesh during the lockdown period of COVID-19 pandemic of 2020: report of a cross-sectional survey - Subhasish Das; Tahmeed Ahmed; Md Ashraful Alam; John D Clemens; Md. Golam Rasul; Md Shabab Hossain; Ar-Rafi Khan (BMJ Open)
Introduction We conducted a cross-sectional survey to assess the extent and to identify the determinants of food insecurity and coping strategies in urban and rural households of Bangladesh during the month-long, COVID-19 lockdown period.Setting Selected urban and rural areas of Bangladesh.Participants 106 urban and 106 rural households.Outcome variables and method Household food insecurity status and the types of coping strategies were the outcome variables for the analyses. Multinomial logistic regression analyses were done to identify the determinants.Results We found that around 90% of the households were suffering from different grades of food insecurity. Severe food insecurity was higher in urban (42%) than rural (15%) households. The rural households with mild/moderate food insecurity adopted either financial (27%) or both financial and food compromised (32%) coping strategies, but 61% of urban mild/moderate food insecure households applied both forms of coping strategies. Similarly, nearly 90% of severely food insecure households implemented both types of coping strategies. Living in poorest households was significantly associated (p value <0.05) with mild/moderate (regression coefficient, β: 15.13, 95% CI 14.43 to 15.82), and severe food insecurity (β: 16.28, 95% CI 15.58 to 16.97). The statistically significant (p <0.05) determinants of both food compromised and financial coping strategies were living in urban areas (β: 1.8, 95% CI 0.44 to 3.09), living in poorest (β: 2.7, 95% CI 1 to 4.45), poorer (β: 2.6, 95% CI 0.75 to 4.4) and even in the richer (β: 1.6, 95% CI 0.2 to 2.9) households and age of the respondent (β: 0.1, 95% CI 0.02 to 0.21).Conclusion Both urban and rural households suffered from moderate to severe food insecurity during the month-long lockdown period in Bangladesh. But, poorest, poorer and even the richer households adopted different coping strategies that might result in long-term economic and nutritional consequences.